A Diazeniumdiolate Signal in Pseudomonas syringae Upregulates Virulence Factors and Promotes Survival in Plants - Qiang Guo; Caitlin N. Vitro; Drake M. Crawford; Bo Li (Molecular Plant-Microbe Interactions)
Pseudomonas syringae infects a wide variety of crops. The mangotoxin-generating operon (mgo) is conserved across many P. syringae strains and is responsible for producing an extracellular chemical signal, leudiazen. Disruption of the mgoA gene in P. syringae pv. syringae (Pss) UMAF0158 alleviated tomato chlorosis caused by this bacterium. We showed that deletion of the entire mgo reduced Pss UMAF0158 population in tomato leaflets. Leudiazen restored the signaling activity of the deletion mutant at a concentration as low as 10 nM. Both the diazeniumdiolate and isobutyl groups of leudiazen are critical for this potent signaling activity. Transcriptional analysis showed that mgo and leudiazen induce the expression of mangotoxin biosynthetic operon as well as an uncharacterized gene cluster, RS17235–RS17245. We found that this cluster enhances the survival of Pss UMAF0158 in planta and is widely distributed in P. syringae strains. Our results demonstrate that mgo plays prominent roles in the virulence and growth of P. syringae. The mgo and mgo-like signaling systems in different bacteria likely regulate diverse microbe-host interactions. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.